Earth Observation and Economic Studies: A Cross-fertilization Perspective. (August 2021) - Florio, Massimo; Morretta, Valentina
Abstract: Over the past decade, an increasing number of satellite images and other earth observation (EO) data have become available to a wide range of final users, including economists and other social scientists, boosting the amount of information they can obtain to study, analyze, and manage different research topics in their fields. In turn, economists are promoting advancement in the quantification of the benefits related to the increasing use of EO services and applications by governments, firms, and citizens. Drawing from recent literature, and our own research, we explore, on one side, how social scientists, and particularly economists, can significantly benefit from EO data, and conversely, how socio-economic impact studies of EO can take advantage from a specific set of economic methods. This article suggests that cross-fertilization and interplay between economics, social sciences, and remote sensing science are needed to advance understanding of our societies and to more rigorously evaluate the socio-economic impact of EO services and applications. The article suggests possible new research avenues.